KARAKTER RELIGIUSITAS PADA TEATERIKAL KHUTBAH JUMAT DI MESJID TUA GANTARANG LALANGBATA KEPULAUAN SELAYAR - Andi Taslim Saputra (Universitas Negeri Makassar, 2024)
The events surrounding Islamic expansion in the Selayar Islands have a different character, especially the beginning of Islamic expansion in the Gantarang Lalangbata area. This religious expansion is accompanied by the cultural capital of theatrical expression, which is carried out every Friday. The focus of this research is on the Friday sermon, which took place at the historic mosque in Gantarang Lalangbata, Selayar Islands. The phenomenon of religiosity is studied in this research using the social psychology theory of three-dimensional analysis as a tool. We can find support for the research findings in this analysis technique. The research findings based on the analysis previously described are the search for the religiosity characteristics of this phenomenon. The Islamic narrative is hinted at and enforced by this incident in the theatre, which is an important part of the Friday sermon at the Gantarang Lalangbata Old Mosque. This is also an important part of the findings of the three dimensions of psychological analysis. Based on research, the way the Friday sermon is carried out shows that the character played has a religious personality based on physical, psychological, and social findings.